Studies on antimicrobial effect of natural dyes and pigments obtained from the leaf of Artocarpus heterophyllus Lam. and Tectona grandis L.f. - Basanti Majhi; Kunja Bihari Satapathy; Sagar Kumar Mishra; Ashirbad Mohapatra (International Journal of Phytomedicine, 2015)
At present there is a renewed interest for value addition of textiles by using natural products. Many of the plant materials, from which natural dyes are obtained, also found to have some medicinal values. However, it is a matter of concern that the indigenous knowledge of extraction, processing and practice of using natural dyes has diminished to a great extent among the new generation of ethnic people due to easy availability of cheap synthetic dyes. In view of this, the present study was undertaken so as to revive and popularise the age-old art of dyeing with natural dyes. During the investigation dyeing materials were prepared from leaves of Artocarpus heterophyllus Lam. (Jack fruit) and Tectona grandis L.f. (Teak). Silk fabrics were dyed with the extracted colouring materials and were estimated for their wash fastness to ensure the durability of the colour on the fabrics. Finally, the antimicrobial effect of the two different natural dyed fabrics was studied against Klebsiella pneumoniae, Escherichia coli, Candida albicans and Aspergillus sp. The dye prepared from leaves of Tectona grandis L.f. was found to be most effective by showing maximum zone of inhibition as compared to Artocarpus heterophyllus Lam. The textile material impregnated with two natural dyes resulted in the maximum zone of inhibition rate (65%) against Escherichia coli as recorded in the silk samples dyed with Tectona grandis. It can be concluded that the natural dyes obtained from these two plants under study could provide special aesthetic values, which is not only environmentally friendly but gives added qualities to the textile production because of the antimicrobial potential of the dyes.